2016
DOI: 10.1038/onc.2016.193
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3 is a key downstream regulator of p53-mediated cellular senescence

Abstract: The downstream events and target genes of p53 in the process of senescence are not fully understood. Here, we report a novel function of the forkhead transcription factor Foxp3, which is a key player in mediating T-cell inhibitory functions, in p53-mediated cellular senescence. The overexpression of Foxp3 in mouse embryonic fibroblasts (MEFs) accelerates senescence, whereas Foxp3 knockdown leads to escape from p53-mediated senescence in p53-expressing MEFs. Consistent with these results, Foxp3 expression resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…However, it has been reported to be expressed in other types of cells such as B cells and cancer cells, and the function is still controversial . Previous studies have reported that FOXP3 is a downstream target gene of TP53, and TP53 can upregulate the expression level of FOXP3 . Our data indicated that the proliferating marker genes PCNA and Ki67 (Figure C,D) as well as TP53 and LC3B was upregulated after knockdown of FOXP3 (Figure C‐E).…”
Section: Discussionmentioning
confidence: 54%
“…However, it has been reported to be expressed in other types of cells such as B cells and cancer cells, and the function is still controversial . Previous studies have reported that FOXP3 is a downstream target gene of TP53, and TP53 can upregulate the expression level of FOXP3 . Our data indicated that the proliferating marker genes PCNA and Ki67 (Figure C,D) as well as TP53 and LC3B was upregulated after knockdown of FOXP3 (Figure C‐E).…”
Section: Discussionmentioning
confidence: 54%
“…Our functional study results showed that the ectopic expression of FOXP3 inhibited proliferation, migration and invasion of HCC cells (Hep3B and PLC/PRF/5), but increased the apoptotic population. It has been reported that FOXP3 is a key downstream regulator of p53-mediaetd cellular senescence in breast cancer cells 26 . Our data suggested that p53 may involve in the FOXP3-induced apoptosis in PLC/PRF/5 cells.…”
Section: Discussionmentioning
confidence: 99%
“…FOXP3 protein is a number of forkhead/winged helix families and has been recovered to function as suppresser of many cancers . Mir‐198 is a 22 bases RNA which regulates many proteins expression by interfering their translation .…”
Section: Discussionmentioning
confidence: 99%